2021
DOI: 10.3389/fnins.2020.607711
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Akt in Hypoxia Adaptation in Andeans

Abstract: Chronic mountain sickness (CMS) is a disease that potentially threatens a large segment of high-altitude populations during extended living at altitudes above 2,500 m. Patients with CMS suffer from severe hypoxemia, excessive erythrocytosis and neurologic deficits. The cellular mechanisms underlying CMS neuropathology remain unknown. We previously showed that iPSC-derived CMS neurons have altered mitochondrial dynamics and increased susceptibility to hypoxia-induced cell death. Genome analysis from the same po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…In the present study, we observed that mTORC2 appears to be active and phosphorylates Akt kinase under hypoxic conditions. Overall, our observations are consistent with previously published studies [ 48 , 49 ]. One interesting study suggests that mTORC2 may mediate several processes associated with migration, invasion and survival through PLD activation due to stress-dependent serum withdrawal.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we observed that mTORC2 appears to be active and phosphorylates Akt kinase under hypoxic conditions. Overall, our observations are consistent with previously published studies [ 48 , 49 ]. One interesting study suggests that mTORC2 may mediate several processes associated with migration, invasion and survival through PLD activation due to stress-dependent serum withdrawal.…”
Section: Discussionsupporting
confidence: 94%
“…It is proposed that increased Akt activation protects against hypoxia-induced cell death. Therefore, it is suggested that impaired adaptive mechanisms, including lack of Akt activation and increased Parkin expression, render neurons from chronic mountain sickness subjects more susceptible to hypoxia-induced cell death [ 99 ].…”
Section: Signaling Pathways Interacting With Hifsmentioning
confidence: 99%
“…Recent studies have found that serum ferritin levels tend to rise with increasing OSA severity ( 13 ). Chronic intermittent hypoxia is the signature manifestation of OSA, and intermittent hypoxia in the brain will lead to excessive accumulation of reactive oxygen species (ROS) in neurons, which may cause permanent death of neurons ( 14 ). Recent studies have shown that hypoxia can increase the iron content in the brain of animals leading to neurodegeneration, and disorder the metabolism of nerve cells by affecting the ferroptosis-related to genes, resulting in excess oxygen free radicals ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%